Topotecan for the treatment of ovarian cancer - Wcisło, Gabriel; Bodnar, Lubomir; Miedzińska-Maciejewska, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2003)
Ovarian cancer is one of the most frequent cancers in women. The lack of early signs and symptoms during ovarian cancer onset is the main culprit to detect the ovarian cancer at advanced stage. Despite the high response rates after the initial paclitaxel plus platinum regimen as the first-line therapy, most of these patients further relapse. There has not been established a consensus on a therapy in recurrence so far. In most published studies the number of patients is too small to determine whether such a topotecan treatment is of the best efficacy and tolerability. This article reviews studies dealing with the use of topotecan in advanced ovarian cancer patients. Topotecan is a topoisomerase I inhibitor that has been lately approved for the treatment of recurrence of ovarian cancer. In the second-line treatment with topotecan monotherapy the overall response rate is more than 20%, and the medium survival time is a year and a half. In an effort to maximise the effectiveness of the treatment, topotecan is combined in sequential setting or schedules with different drugs that have demonstrated their activity in recurrent disease, including paclitaxel, etoposide, cisplatin, carboplatin, cyclophosphamide, doxorubicin and cytarabine. The haematological toxicity profile needs to be monitored carefully for patients’ safety with proper activity when it occurs. Phase III studies are about to clarify the usage of topotecan in a particular mode of ovarian cancer therapy. It is necessary to find out what role topotecan plays in first-line therapy but to this end more clinical trials must be carried out.